Physicochemical and sensory attributes of Trihoney blend (Trigona sp., Apis mellifera, and Apis dorsata) for enhanced antioxidant optimization using Response surface methodology (RSM) - Abdul Rafa, Ainin Azwani; Ibrahim, Muhammad; Zakaria, Nor Hafizah; Anuar, Mohd Nur Nasyriq; Mat Alewi, Nur Aizura; Abdul Ghani, Radiah; Abdul Majid, Fadzilah Adibah (IIUM Press, 2024)
NTRODUCTION: The therapeutic applications of honey products have been extensively studied, but the various combination of honeys as a high-antioxidant product has not been explored. This study aimed to develop an optimized three honey formulation (Trihoney) with maximal antioxidant potency and physicochemical characteristics, as well as favourable among panellists. MATERIALS AND METHODS: The three types of honey studied are; i) Trigona sp. honey (TH), ii) Apis mellifera honey (MH), and iii) Apis dorsata honey (DH). Response surface methodology (RSM) was employed to design optimal Trihoney formulation for i) total phenolic content (TPC), ii) ferric-reducing ability of plasma (FRAP), and iii) 2,2’-diphenyl-1 picrylhydrazyl (DPPH) radical scavenging activity. Proximate and nutrient analyses, such as moisture, protein, fibre, carbohydrate, sugar, and gross energy were also conducted. Additionally, sensory evaluation was carried out to support the findings. RESULTS: Based on RSM, three optimal Trihoney formulation were developed; i) Trihoney 1 (MH15:DH10:TH45), ii) Trihoney 2 (MH15:DH10:TH25), and iii) Trihoney 3 (MH15:DH10:TH15). Trihoney 1 was the most promising formulation, exhibiting the highest TPC (0.50 mg/GAE/g), remarkable values of FRAP (230.85 AAE/ g) and DPPH (86.32%). Physicochemical and sugar analysis indicated that all values complied with permitted quality standards. MH received the highest overall acceptability scores based on sensory evaluation. CONCLUSION: These findings warrant further extensive investigation of Trihoney formulation in animal studies to support its efficacy a valuable food supplement